Waterborne Pathogens: A Critical Assessment of Methods, Results and Data Analysis - Payment, Pierre; Pintar, Katarina (Revue des sciences de l'eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2006)
SummaryHumans harbour a variety of pathogens that are often transmitted from other animal species. A few are localized in tropical areas, but most enteric pathogens are present everywhere on the planet and they travel with their hosts to distant locations. Several of these microorganisms are transmitted by water that has been contaminated by fecal matter, whereas some are normally found in water but, given an opportunity, will cause disease (i.e., opportunistic pathogens). While waterborne outbreaks have been reported for many pathogens, assessing the proportion of the disease burden to a specific route and pathogen has proven quite elusive. Surveillance of disease in populations, even when actively done, is very inaccurate as it often gathers data on the most acute cases that are only a very small proportion of the true number of infected individuals. There are several issues discussed herein, focusing on the needs and gaps linked to waterborne pathogen monitoring. The benefits and weaknesses of current and emerging methodologies are discussed, in addition to the appropriateness of allocating resources to waterborne pathogen monitoring. The most critical gap is the lack of validation of most methods used in environmental microbiology for the detection of pathogens. Data generated by various laboratories are currently extremely difficult to compare and cannot serve as the basis for risk assessment or management. The issue of laboratory capacity is also raised, within the context of the availability of trained personnel, the application of QA/QC protocols, and accreditation on a national level. In closing, needs are identified for informed communication of the risks of waterborne pathogens, the training of highly qualified personnel, and the development and standardization of methods that will ultimately enhance water safety and public health protection.